2014
DOI: 10.1089/neu.2014.3356
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognition in the Emergency Department after a Mild Traumatic Brain Injury in Youth

Abstract: The early cognitive effects from a mild traumatic brain injury (mTBI) are poorly understood in youth. The aim of this study was to examine acute neurocognitive functioning in children and adolescents who presented to the emergency department (ED) after an mTBI. Youth 8-17 years of age with an mTBI (n=77; mean age, 13.6 years; 95% confidence interval [CI], 13.0-14.2) and an orthopedic injury control (OIC) group (n=28; mean age, 13.9 years; 95% CI, 13.1-14.7) underwent a very brief computerized neurocognitive as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…CNSVS domain scores generally have medium to large correlations with more conventional neuropsychological measures used in youth populations (Plourde, Hrabok, Sherman, & Brooks, 2018) and marginal (r = .63) to high (r = .82) test-retest reliabilities (Brooks & Barlow, 2011). CNSVS has sensitivity in samples with mixed neurological disorders , concussion (Brooks, Khan, Daya, Mikrogianakis, & Barlow, 2014), and moderate to severe traumatic brain injury (TBI) (Plourde & Brooks, 2017) and is part of the NINDS pediatric brain injury common data elements (McCauley et al, 2012). CNSVS domain scores have a normalized mean of 100 (SD = 15) based on a standardized sample.…”
Section: Cognitive Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…CNSVS domain scores generally have medium to large correlations with more conventional neuropsychological measures used in youth populations (Plourde, Hrabok, Sherman, & Brooks, 2018) and marginal (r = .63) to high (r = .82) test-retest reliabilities (Brooks & Barlow, 2011). CNSVS has sensitivity in samples with mixed neurological disorders , concussion (Brooks, Khan, Daya, Mikrogianakis, & Barlow, 2014), and moderate to severe traumatic brain injury (TBI) (Plourde & Brooks, 2017) and is part of the NINDS pediatric brain injury common data elements (McCauley et al, 2012). CNSVS domain scores have a normalized mean of 100 (SD = 15) based on a standardized sample.…”
Section: Cognitive Testingmentioning
confidence: 99%
“…In the present study, select domains scores for verbal memory, reaction time, and cognitive flexibility were used. These measures have previously been shown to differentiate youth with concussions from youth with OI in the emergency department (Brooks et al, 2014).…”
Section: Cognitive Testingmentioning
confidence: 99%
“…There are limited comparable data on neurocognitive testing in the ED, with most assessments occurring in the sub-acute time period. In similar studies, results have been mixed, with slower reaction times being demonstrated by the majority, [10][11][12] but not all studies. 13 Visual memory dysfunction was also found in mTBI patients; 12,13 however, equivocal findings have also been noted.…”
Section: Discussionmentioning
confidence: 99%
“…Visual memory dysfunction was also found in mTBI patients; however, equivocal findings have also been noted . Measures of executive functioning are not commonly included in acute testing; with just one previous study finding no differences between mTBI and orthopaedic controls on the CNS Vital Signs computerised battery Stroop task and shifting attention tests . The potential challenge faced in evaluating executive dysfunction across studies is that the complexity of this cognitive construct makes it difficult to operationalise a standard definition and method for its testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation